2008
DOI: 10.1002/asia.200800131
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Helical Structure of Poly(1‐methylpropargyl ester)s with Various Side Chains

Abstract: Optically active 1-methylpropargyl esters bearing various substituents were polymerized with [(nbd)Rh](+)[eta(6)-C(6)H(5)B(C(6)H(5))(3)](-) (nbd=norbornadiene) as a catalyst to afford the corresponding poly(1-methylpropargyl ester)s with moderate molecular weights in good yields. The polymers have a cis-stereoregular structure, which was determined by (1)H NMR spectroscopy. Large optical rotations and clear CD signals demonstrated that all these polymers take on a helical structure with a predominantly one-han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
1
16
1
Order By: Relevance
“…Since the UV–vis spectral peaks of poly( 1 )‐poly( 3 ) decreased, it seems that poly( 1 ) and poly( 3 ) changed formation from helix to random coil by heating. It seems that poly( 1 ) and poly( 3 ) underwent thermally driven helix‐random coil transition, which is quite different from the previously reported poly[(S)‐1‐methyl‐propargyl esters]16, 17 that maintained their preference of screw sense on heating. This difference is attributable to azobenzene moieties in the side chain of present polymers, which underwent the trans – cis isomerization reactions with changing the temperature 28…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…Since the UV–vis spectral peaks of poly( 1 )‐poly( 3 ) decreased, it seems that poly( 1 ) and poly( 3 ) changed formation from helix to random coil by heating. It seems that poly( 1 ) and poly( 3 ) underwent thermally driven helix‐random coil transition, which is quite different from the previously reported poly[(S)‐1‐methyl‐propargyl esters]16, 17 that maintained their preference of screw sense on heating. This difference is attributable to azobenzene moieties in the side chain of present polymers, which underwent the trans – cis isomerization reactions with changing the temperature 28…”
Section: Resultscontrasting
confidence: 91%
“…We have recently found that ( R )‐ and ( S )‐1‐methylpropargyl alcohols and its ester derivatives undergo polymerization to give stable helical polymers 16. Further, we have found the poly[( S )‐1‐methylpropargyl esters] exhibited a positive CD signal at around 330 nm has a right‐handed tight helical structure with a dihedral angle at the single bonds in the main of 70° 17. We also synthesized similar polymers carrying carbazole, triphenylamine,18 cholesteryl,19 and pyrene moieties 20.…”
Section: Introductionmentioning
confidence: 97%
“…Poly[( S )‐ 1 ] has high helix‐forming ability even in these polar solvents unlike poly( N ‐butynylamide)s and poly( N ‐propargylamide)s. The remarkable helix induction is probably due to the location of stereogenic centers close to the main chain. Namely, it is considered that the presence of chiral groups in close proximities to the main chain is quite effective to induce a helix stabilized by steric repulsion between the side chains, in a fashion similar to poly(1‐methylpropargyl alcohol)s,53 poly(1‐methylpropargyl ester)s,53, 54 and poly(1‐methylpropargyl‐ N ‐alkylcarbamate)s 17. Poly[( S )‐ 1 ] and poly[( R )‐ 1 ], having side chains with different absolute configurations, exhibited mirror‐image CD spectra at 250–500 nm.…”
Section: Resultsmentioning
confidence: 99%
“…One‐handed helical senses induced through covalent or noncovalent bonding with chiral biases have been reported in a variety of artificial helical polymers 7–9. The chiral amplification following “sergeants and soldiers” and “majority rule” effects have also been observed in a variety of helical polymers, such as polysilanes and polyacetylenes 6–8, 10…”
Section: Introductionmentioning
confidence: 96%